TANDA NASHOB YA dan HIKMAH NYA BAGI KEHIDUPAN MASYARAKAT - Uzmi, Muhammad Fadil; Aprilla, Nurul (Jurnal Al-Hibru, 2025)
Grammar is essential for the understanding and meaning of each language. Nashab is one of the most important types of i'rab. Nouns or verbs can function as direct objects, adverbs, or places, or have other grammatical functions in a sentence, according to Nashab. Understanding the nashab well is not only important for linguistic accuracy, but it is also essential for text interpretation, communication, and even many other aspects of people's lives. The nashab sign indicates that the word is in a state of manshub (nashab), which means that the word serves as a direct object, indirect object, or complement in a sentence. In simple terms, nashab signs provide information about the function or role of words in sentences. In this study, the author analyzed various literature related to learning, such as journals, theses, books, and others, to see the signs on the text. This research aims to study the signs of nashab ya in daily life, including its meaning, role, and meaning.